Cardio-Renal Syndrome:Mechanistic Review - Dumler, Francis (2022)
The Cardio-Renal Syndrome (CRS) is a multi-organ disease process characterized by joint cardiac, renal, and vascular systems dysfunction magnified by abnormal "cross talk" between body systems which are necessary for optimal equilibrium and functioning of the whole organism. There are five phenotypes:  type-1 (Acute Cardio-Renal); type-2 (Chronic Cardio-Renal); type-3 (Acute Reno-Cardiac); type 4 (Chronic Cardio-Renal); type-5 (Secondary Cardio-Renal). Type-1 is the most common type (50% of cases). Acute heart failure decreases cardiac output and reduces renal blood flow, effective glomerular perfusion, filtration pressure, and glomerular filtration rate. Type-2 is the second most common (20% of cases). Chronic heart failure results in chronic hypoperfusion which causes/aggravates chronic kidney disease. In Type-3, acute kidney injury causing volume overload which triggers acute heart failure. In Type-4, chronic kidney disease, a serious comorbid factor, significantly increases the risk for developing /worsening chronic heart disease and failure.  In Type-5, systemic disease processes, whether acute or chronic, may cause simultaneous cardiac and renal dysfunction. The disease in one may then worsen the other and vice versa. These dysfunctions are mediated by circulating pro-inflammatory and pro-apoptotic mediators, as in severe sepsis and autoimmune disorders. The treatment of CRS is confounded by multiple and interrelated pathophysiologic mechanisms and by the conflicting impact of therapies on multiple organs. What benefits one organ may be detrimental to its counterpart and vice versa. Paradigms for management for volume overload, acute decompensated heart failure, pharmacologic and extracorporeal therapies as well as other modes of support therapy are outlined and discussed.